Design of a low cost measurement system based on accelerometers for gait analysis - doi: 10.4025/actascitechnol.v36i1.18581 - Martínez-Solís, Fermín (2014)
Current research reports on the development of a portable electronic system to assess the kinematics of the lower limb joints at the sagittal plane. The electronic device characteristics and the different communication protocols to transfer data are also reported. Research obtained the hip and knee angles to analyze the lower limb kinematics during multiple gait cycles. Results showed that the movement patterns, found in the analysis made on people from central Mexico, were cyclical and alternating. The knee described a one third curve in flexion-extension movements just before the start of the flexion-extension curve in the swing phase. Moreover data obtained showed a correlation of movement between hip and knee during walking.